Cardiac shear-wave elastography using a transesophageal transducer: application to the mapping of thermal lesions in ultrasound transesophageal cardiac ablation. (25th September 2015) - Kwiecinski, Wojciech; Bessière, Francis; Colas, Elodie Constanciel; Apoutou N'Djin, W; Tanter, Mickaël; Lafon, Cyril; Pernot, Mathieu
Abstract: Heart rhythm disorders, such as atrial fibrillation or ventricular tachycardia can be treated by catheter-based thermal ablation. However, clinically available systems based on radio-frequency or cryothermal ablation suffer from limited energy penetration and the lack of lesion's extent monitoring. An ultrasound-guided transesophageal device has recently successfully been used to perform High-Intensity Focused Ultrasound (HIFU) ablation in targeted regions of the heart in vivo . In this study we investigate the feasibility of a dual therapy and imaging approach on the same transesophageal device. We demonstrate in vivo that quantitative cardiac shear-wave elastography (SWE) can be performed with the device and we show on ex vivo samples that transesophageal SWE can map the extent of the HIFU lesions. First, SWE was validated with the transesophageal endoscope in one sheep in vivo . The stiffness of normal atrial and ventricular tissues has been assessed during the cardiac cycle ( ) and mapped ( ). Second, HIFU ablation has been performed with the therapy-imaging transesophageal device in ex vivo chicken breast samples (n  =  3), then atrial (left, ) and ventricular (left, right ) porcine heart tissues. SWE provided stiffness maps of the tissues before and after ablation. Areas of the lesions were obtained by tissue color change with gross pathology and compared to SWE. During the cardiac cycle stiffness varied from 0.5   ±   0.1 kPa to 6.0   ±   0.3 kPa in the atrium and from 1.3   ±   0.3 kPa to 13.5   ±   9.1 kPa in the ventricles. The thermal lesions were visible on all SWE maps performed after ablation. Shear modulus of the ablated zones increased to 16.3   ±   5.5 kPa (versus 4.4   ±   1.6 kPa before ablation) in the chicken breast, to 30.3   ±   10.3 kPa (versus 12.2   ±   4.3 kPa) in the atria and to 73.8   ±   13.9 kPa (versus 21.2   ±   3.3 kPa) in the ventricles. On gross pathology, the size of the lesions ranged from 0.1 to 1.5 cm 2 in the imaging plane area. Elasticity-estimated depths and widths of the lesions differed respectively with a median of 0.2 mm (first quartile Q1:  −0.8 mm; third quartile Q3: 2.6 mm) for a mean squared error (MSE) of 5.1 mm 2 and a median of 0.2 mm (Q1:  −2.7 mm; Q3: 2.7 mm) for a MSE of 11.1 mm 2 from gross pathology. We have demonstrated the feasibility of the HIFU thermal ablation monitoring using a dual therapy and imaging transesophageal device. The combination of HIFU, ultrasound imaging and SWE on the same transesophageal system could lead to a new clinical device for a safer and controlled treatment of a wide variety of cardiac arrhythmias.